'A guided walk in the woods': boundary crossing in a collaborative action research project. Issue 4 (8th August 2017) - Jacobs, Gaby
Abstract: This article discusses the ideal and practice of collaboration in a collaborative action research project in which university researchers work together with staff from the field of primary education. A qualitative case study was conducted using the theory of boundary crossing to make sense of the ways collaboration took place within the project team. The main theme, also a major dilemma in the project, referred to the transition from a democratic towards a more directive approach within the project design after the first year. The members of the project team took shifting and ambivalent positions within the project as they were trying to cross boundaries between the different goals of the project. Also, boundary objects on different levels contributed to the collaboration. We conclude that clear boundaries between groups or a strong shared identity, as proposed by an insider–outsider model of action research and the notion of first-order democracy, are not helpful in complex collaborative action research projects. Instead, we need the development of second-order democracy means in order to cross boundaries and sustain a critical dialogue about differences.